2022
DOI: 10.31219/osf.io/qux6g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jittering: A computationally efficient method for generating realistic route networks from origin-destination data

Abstract: Origin-destination (OD) data is a vital source of information on travel patterns but its utility is limited by reliance on zone centroids. This paper presents a reproducible and open two-stage ‘jittering’ approach to tackling this problem, which (1) uses random points to represent unique start and end points (sampling), and (2) splits OD pairs representing many trips into many ‘sub-OD’ pairs. We find that route networks generated from jittered OD data are more diffuse and potentially realistic based on an exam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Building on previous work (Lovelace et al, 2022b), we have explored the relative importance of jittering and routing options for generating accurate route network level estimates of movement, down to the street level. In corroboration with previous research, we found that jittering leads to more spatially diverse geographic representations of travel between zones and estimates of flow down to the link level (Lovelace et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Building on previous work (Lovelace et al, 2022b), we have explored the relative importance of jittering and routing options for generating accurate route network level estimates of movement, down to the street level. In corroboration with previous research, we found that jittering leads to more spatially diverse geographic representations of travel between zones and estimates of flow down to the link level (Lovelace et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…The overall result was the finding that OD jittering methods first developed by Lovelace et al (2022b) are not enough on their own to generate accurate route networks. Jittering leads to more spatially diffuse route networks than networks generated from the common approach of routing from and to zone centroids.…”
Section: • Estimates Of Quietness Of Links On the Network Computedmentioning
confidence: 99%
See 3 more Smart Citations